Total School Theory as Framework for Promoting Quality Assurance in Federal University Dutsin-Ma, Katsina State, Nigeria - BUSA, Abdul’aziz Inusa; GODFREY, Gayus Shown; SHAMSUDDEEN, Salisu (Ilorin Journal of Education, 2025)
This study explores the application of the Total School Theory (TST) as a framework for promoting quality assurance in educational institutions, with specific insights from Federal University Dutsin-Ma (FUDMA), Katsina State, Nigeria. The researcher used descriptive survey research design. The population is about one thousand seven hundred and fifty-four (1754) academic staff across the 13 faculties in the University. Data were collected from 439 academic staff across 13 faculties using a validated questionnaire. Three research questions were raised for the study. Total School Theory as Framework for Promoting Quality Assurance in Federal University Dutsin-Ma, Katsina State questionnaire (TSTFPQAEIQ) and a structured questionnaire was employed to gather data. The instrument was validated by two experts. One from Educational administration and planning, and the other from Measurement and Evaluation, of Psychology and Counselling Departments, Federal University Dutsin-Ma, Katsina State. The research questions were answered using mean and standard deviation, and a mean of 2.50 was taken as the landmark for taken decision and below 2.50 was taken as rejection. The findings suggest that FUDMA can further enhance its quality assurance practices by leveraging TST principles. This includes fostering participatory decision-making, integrating technology for monitoring outcomes, and establishing a robust feedback system involving all stakeholders. The following recommendations were made; FUDMA should institutionalize TST principles by aligning its policies and practices with a holistic, systemic, and collaborative framework to enhance overall quality assurance, and Administrators should actively involve faculty, students, and external stakeholders in decision-making and quality improvement initiatives to foster shared responsibility.